ADVANCED MATHEMATICS FORM 5 – ALGEBRA

Share this post on:

Remainder and factor theorem

Definition:

              A polynomial is an expression of the form

            anxn + an – 1 x n – 1 + an – 2 x n -2 + …… + a1x + a0

            Where an, an – 1, an – 2 …a1, ao are real numbers known as coefficients of the polynomial

            →an
edu.uptymez.com 0

            →anxn is the leading term

            →n is called the degree of the polynomial

Normally the polynomial is written as p (x) = anxn + an – 1xn– 1+ … + a1x + ao

            P (x) = anxn + an – 1xn -1 + …. + a1x + ao

e.g.

        p (x) = 2x4 – 3x3 + 10x3 + 10x2 – x + 11

        p (x) = x5

        p (x) = 2x2 – 3x + 10

        p (x) = 6x3 – 22x2 – 12

        p(x) = 3x – 2

        p (x) = 17

To divide a polynomial p (x) by another polynomial D (x) means finding polynomial Q (x) and r (x)

Such that

            P (x) = D (x) Q (x) + r (x)

edu.uptymez.com 

Where p (x) is called a dividend

              Q (x) is called a quotient

              D (x) is called divisor

              r (x) is called remainder

Note that the degree of r (x) < D(x)

The remainder theorem

When a polynomial p (x) is divided by a linear factor (x – a) the remainder is P (a)

When a linear factor is in the form kx – b then it should be put in the form k(x – edu.uptymez.com) and the remainder is then P (edu.uptymez.com)      

Proof:

Let P (x) = (x – a) Q(x) + R

Where Q (x) is a polynomial and R is the remainder when x = a

→P (a) = (a – a) Q (a) + R

           P (a) = R

             R = P (a)                                                                                                                

When R = 0

            P (x) = (x – a) Q(x)

                        x – a is a factor or p (x)

Since p (a) = 0

            ”a” is a root (a zero) of p(x)

Examples

1.  Find the remainder when x5 + 4x4 – 6x2 + 3x + 2 is divided by x + 2

            Solution

            P (x) = x5 + 4x4 – 6x2 + 3x + 2

            x – a = x + 2

                        a = -2

            p(-2) = (-2) 5 + 4(-2)4 – 6 (-2) 2 + 3x – 2 + 2

            p(-2) = -32 + 64 – 24 – 6 + 2

                        = 66 – 62

                        = 4

            P(-2) = 4

2.   Find the remainder when 4x3 – 6x2 – 5 is divided by 2x – 1

            Solution

            P (x) = 4x3 – 6x2 – 5

            x – a = (x – ½)

            P edu.uptymez.com = 4edu.uptymez.com – 6 x edu.uptymez.com – 5

            = edu.uptymez.com

            = 1 – 3 – 10
2

            P (edu.uptymez.com) = -6

Factors theorem

If ‘a’ is a zero of p (x) then (x – a) is a factor of p(x) i.e. p(x) = (x – a) Q (x)

Proof:

            Let p (x) = (x – a) Q(x) + R

            Given ‘a’ is a zero of p (x)

            Then p(a) = 0

                         0 = (a – a) Q (a) + r

                          0 = r

                          r = 0

            p (x) = (x – a) Q(x)

              x – a is a factor of p (x)

Examples

Factorize completely the following polynomial function x4 – 5x3 + 6x2 + 2x – 4

Solution

Let p(x) = x4 – 5x3 + 6x2 + 2x – 4

            P (1) = 1 – 5 + 6 + 2 – 4

                        = 0

            P (2) = 24 – 5 (2)3 + 6 (2) 2 + 2 x 2 – 4

                        = 16 – 40 + 24 + 4 – 4

                        = 0

            (x – 1) and (x – 2) are factors of P (x)

                        →P (x) = (x – 1)(x – 2) Q(x)

                        P (x) = (x2 – 3x + 2) Q(x)

       edu.uptymez.com

Q (x)   = x2 – 2x – 2

= (x2 – 2x + 1) – 3

edu.uptymez.com

= ((x – 1) +edu.uptymez.com) ((x – 1) –edu.uptymez.com)

→P (x) = (x – 1) (x – 2) (x – 1) +edu.uptymez.com) (x – 1) –edu.uptymez.com)

Synthetic division

Synthetic division is the shortcut method to find the remainder when a polynomial function is divided by a factor x – a

Example

1.  Use synthetic division to divide 2x3 + x2 – 3x + 4 by x + 3

            Solution

            x – a = x + 3

            So; a = -3

            Then                    

                           edu.uptymez.com

Note that in the synthetic division the third row will contain the coefficients of the quotient and the remainder

2.  Use synthetic division to divide 4x3 – 6x2 – 5 by 2x -1

Solution

                        x – a = 2x – 1

                                   a = ½

                                 edu.uptymez.com

                        Q (x) = 4x2 – 4x – 2

                        Remainder = -6

Rational zero theorem

Let p (x) = anxn + an – 1xn – 1 + ….. + ax + ao

Where

            an, an – 1, a1, a0 are integral coefficients and

Let edu.uptymez.com be a rational number in its lowest term

Then if is edu.uptymez.com a zero of p (x) when       p is a factor of a0

                                                             q   Is a factor of an

Example

To find zero of 2x3 – x- 3

If edu.uptymez.com is a zero of the expression

Then p is a factor of -3 ie -1, 1, -3, 3

                                       2 i.e. 1, -1, 2, -2

We try -1, 1, -3, 3, edu.uptymez.com, ½, -3/2, and 3/2

Partial fraction (decomposition of fraction)

The process of decomposition of fraction depends on one of the following;

1)To every linear factor ax + b in the denominator there corresponds a fraction of the form
edu.uptymez.com                                                                                                                             

2) To every repeated factor like (ax + b)n in the denominator there corresponds n fractions of the form edu.uptymez.com 

3) To every factor of the form anxn + an – 1xn – 1+….. + a1x + a0 in the denominator there correspond fraction of the form edu.uptymez.com

4) If the degree of the numerator is greater than or equal to the degree of denominator, division is ennglish-swahili/courage” target=”_blank”>couraged and the remainder is treated as in (1), (2) 0r (3)

Examples

1.  Express in partial fraction

                                            edu.uptymez.com             

            Solution

            Let edu.uptymez.com

            Where A and B are constant

            3x + 7 = A (x + 4) + B (x – 2)

            3x + 7 = Ax + 4A + Bx – 2B

            3x + 7 = (A + B) x + 4A – 2B

            3→x = (A + B) x

            3 = A + B…. (i)

            7 = 4A – 2B…. (ii)

            2 (i) + (ii) gives

            13 = 6A → A = edu.uptymez.com

            From (i)

                        3 =  edu.uptymez.com + B                                                                                                                                           

                        18 = 13 + 6B

                        5 = 6B

                        B = edu.uptymez.com

edu.uptymez.com

2.         edu.uptymez.com    

            Solution

                        edu.uptymez.com 

            x2 + 1 ≡ A (x + 1)3 + B (x + 1)2 (x – 1) + C (x + 1) (x – 1) + D (x – 1)

            When x = 1

                        2 = 8A   →A =edu.uptymez.com         

When x = -1

                        2 = -2D  →    D = -1

            When x = 0

                        1 = A – B – C – D

                        1 = ¼- B – C – (-1)

                        4 = 1 – 4B – 4C + 4

                        1 = 4B + 4C …… (i)

            When x = -2

                        5 = -A – 3B + 3C – 3D

                        5 = –edu.uptymez.com – 3B + 3C + 3

                        20 = -1 – 12B + 12C + 12

                        9 = -12B + 12C

                        edu.uptymez.com

                        4 = 8C

                        C = ½

            From (ii)

                        3 = -4B + 4 x ½

                        3 = -4B + 2

                        edu.uptymez.com                   

edu.uptymez.com
edu.uptymez.com

QUESTION

4.  Express x4 + x3 – x2 + 1  into partial fraction
(x – 1) (x2 + 1)

Quadratic inequalities

A quadratic inequalities is an inequality of one of the following four types

            ax2 + bx + C < 0

            ax2 + bx + C ≤ 0

            ax2 + bx + C > 0

            ax2 + bx + C ≥ 0      

Where a, b and c are real numbers and a edu.uptymez.com 0

Solving quadratic inequality

Solving quadratic inequality involves changing inequality signs to equal sign to obtain the associated quadratic equation.

E.g. x2 + x – 2 ≤ 0 – quadratic inequality

       x2 + x – 2 = 0 – associated quadratic equation

Example

1. Solving the following inequality

            x2 + x – 2 ≤ 0

            Solution

            x2 + x – 2 = 0

            x2 – x + 2x – 2 = 0

            x (x – 1) + 2 (x – 1) = 0

            X = -2            and     x = 1

   edu.uptymez.com

            Testing the values

                        Test value -3

                        4≤ 0    False

                        Test value – 0

                        -2 ≤ 0 True

                        Test value 2

                        4 ≤ 0   False

                        →-2 ≤ x ≤ 1

2.  Solve the following quadratic inequality

                        X2 – 3 > 2x

            Solution

            X2 – 3 > 2x = x2 – 2x – 3 > 0

            Then,

                        x2 – 2x – 3 = 0

                        x2 + x- 3x – 3 = 0

                        x (x + 1) – 3(x + 1) = 0

                        (x + 1) (x – 3) = 0

                        x = -1 and x = 3

                                        edu.uptymez.com                                                                    

                        Test value -2

                        1 > – 4 → true

                        Test value 0

                        -3 > 0 → false

                        Test value 4

                        13 > 8 = true

                        x < -1    and     x > 3

Exercise

Solve the following inequalities

a)     (x – 2) (x – 1) > 0

b)     (3 – 2x) (x + 5) ≤ 0

c)     (1 – x) (4 – x) > x + 11

d)     edu.uptymez.comx2 – 2x + 3 > 0

e)     3x + 4 < x2 – 6 < 9 – 2x

Rational inequalities

Examples

1.                  Solve the inequality

                        edu.uptymez.com           

            Solution

            1st Make one side equal to 0

               edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com

            Do not multiply by denominator since x – 5 is not known as positive or    negative

            2nd find real numbers that make either the numerator or the denominator equal to 0

            I.e. -2x + 13 = 0
2x = 13

                    X = edu.uptymez.com makes numerator = 0

            And x – 5 = 0

                        X = 5 makes the denominator = 0

                  edu.uptymez.com

            Test value 4

            -5 > 3 → false

            Test value 6

            4 > 3 → true

            Test value 7

            edu.uptymez.com > 3 – false

           =  5 < x <  edu.uptymez.com       

2.      Solve the inequality

edu.uptymez.com

                  Solution

edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com

            X = 6 makes the numerator = 0

            X = 3 makes the denominator = 0


edu.uptymez.com

3.  Find the possible values of x for which edu.uptymez.com

            Solution

edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com

           edu.uptymez.com

Test value P

                        -24 ≤ 0 →True

            Test value -4

            edu.uptymez.com < 0 false                                                                                                                        

            Test value 2

            0 < 0→ true

            Test value 5

            4 < 0 → false

              →2< x < 4

Exercise

 What values of x satisfy in each of the inequalities?

A.    edu.uptymez.com

B.     edu.uptymez.com

C.     edu.uptymez.com

D.    edu.uptymez.com

            Absolute value inequality

            Examples

            Solve the following inequalities

            a) |2x – 3| < 5

            b) |x – 2| > -3

            c) |2x + 3| < 6

            Solution

            a) |2x – 3| < 5

            2x – 3 < 5      or        2x – 3 > -5

            2x < 8                        2x > -2

            x < 4               or            x > -1

  edu.uptymez.com

Examples

Solve the following inequalities

edu.uptymez.com

Solution

edu.uptymez.com
edu.uptymez.com

edu.uptymez.com
edu.uptymez.com
edu.uptymez.com

  edu.uptymez.com  


X < 0,      0.8 < x < 1     and     x > 1

Determinant of a 3 x 3 matrix

Let

edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com
edu.uptymez.com

Share this post on: